Mitochondrial DNA structure of an isolated Tunisian Berber population and its relationship with Mediterranean populations. (2nd January 2018) - Ben Halim, Nizar; Hsouna, Sana; Lasram, Khaled; Chargui, Mariem; Khemira, Laaroussi; Saidane, Rachid; Abdelhak, Sonia; Kefi, Rym
Abstract: Background: Douiret is an isolated Berber population from South-Eastern Tunisia. The strong geographic and cultural isolation characterising this population might have contributed to remarkable endogamy and consanguinity, which were practiced for several centuries. Aim: The objective of this study is to evaluate the mitochondrial DNA (mtDNA) genetic structure of Douiret and to compare it to other Mediterranean populations with a special focus on major haplogroup T. Subjects and methods: Genomic DNA was extracted from blood samples of 58 unrelated individuals collected from the different patrilineal lineages of the population. The hypervariable region 1 of the mtDNA was amplified and sequenced. For comparative analyses, additional HVS1 sequences ( n = 4857) were compiled from previous studies. Results: The maternal background of the studied sample from Douiret was mainly of Eurasian origin (74%) followed by Sub-Saharan (17%) and North African (3%) lineages. Douiret harbours the highest frequency of haplogroup T in the Mediterranean region, assigned to the unique subclade T1a (38%). Phylogenetic analysis showed an outlier position of Douiret at the Mediterranean level. Conclusions: The genetic structure of Douiret highlights the presence of founders, most likely of Near/Middle Eastern origin, who conquered this area during the Middle/Late Upper Palaeolithic and Neolithic dispersals.